MODEL GEMBIRA: SOLUSI INOVATIF UNTUK MENINGKATKAN KETERAMPILAN BERPIKIR KRITIS DALAM MEMBACA PEMAHAMAN PADA SISWA KELAS 4A SDN KUIN SELATAN 1 BANJARMASIN BARAT - Norlidia; Mahmuddin (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The research problem is the low activity and critical thinking skills in reading comprehension among students, which affects their learning outcomes in Indonesian language content. The effort to address this uses the GEMBIRA learning model, which is a combination of three learning models: Problem Based Learning (PBL), Cooperative Integrated Reading And Composition (CIRC), and Teams Games Tournament (TGT). The objective of this research is to describe teacher activity, analyze the increase in student activity, critical thinking skills in reading comprehension, and student learning outcomes. This research uses Classroom Action Research (CAR). The subjects of the study are 20 students from class 4A of SDN Kuin Selatan 1 Banjarmasin Barat, consisting of 7 male students and 13 female students. This study employs both qualitative and quantitative approaches. The results show that teacher activity from meetings 1 to 4 received a very good criterion. The critical thinking skills in reading comprehension from meetings 1 to 4 increased from a less skilled criterion to a very skilled one. Based on the findings, it is concluded that the GEMBIRA learning model can enhance teacher activity, student activity, critical thinking skills in reading comprehension, and student learning outcomes in Indonesian language learning on determining the main ideas and supporting ideas of paragraphs. It is recommended to use this model as an alternative in improving the quality of learning.